Just Public Mausoleums? Museums and Intangible Heritage: A Case-study of the National Museum of Ireland – Country Life - Kingston, Sarah (Irish Journal of Arts Management and Cultural Policy, 2014)
Following an expansion of international conceptions of heritage to include the intangible, it has also been questioned what role museums have to play regarding our living cultural heritage. Using the National Museum of Ireland - Country Life / Ard-Mhúsaem na hÉireann - Saol na Tuaithe (NMI-CL) as a case-study, this research explores why intangible heritage should be incorporated into a national folklife museum, the extent to which this is already being done, and analyses some of the related difficulties. This paper shows that although the museum values and involves intangible heritage, it is treated as secondary to tangible culture and supplementary to the tangible collection, which limits its use in the museum. This paper suggests that engaging intangible heritage in its exhibitions and programming can serve as a one tool to help museums become more engaging and lively institutions. It outlines a story-focussed exhibition and programming approach that would allow tangible and intangible material to be treated as equals, and enable the museum to more closely interweave its many different activities.